2006
DOI: 10.1177/1073191106287354
|View full text |Cite
|
Sign up to set email alerts
|

Callous-Unemotional Traits in a Community Sample of Adolescents

Abstract: This study examined the structure, distribution, and correlates of a new measure of self-reported callous-unemotional (CU) traits in 1,443 adolescents (774 boys, 669 girls) between the ages of 13 to 18 years. The Inventory of Callous-Unemotional Traits was subjected to exploratory factor analysis and confirmatory factor analysis. Exploratory factor analysis produced three factors: callousness, uncaring, and unemotional. Fit indexes suggested that the three-factor model, with a single higher-order factor, repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

105
873
12
15

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 746 publications
(1,005 citation statements)
references
References 69 publications
105
873
12
15
Order By: Relevance
“…Items (e.g., "I do not show my emotions to others") are rated on a 4-point Likert scale from 0 (not at all true) to 3 (definitely true). The construct validity of the ICU was supported in a large community sample (n = 1,443) of 13-to 18-year-old nonreferred German adolescents (774 boys and 669 girls; Essau, Sasagawa, & Frick, 2006), as well as an American sample (n = 248) of male and female juvenile offenders (188 boys, 60 girls) between the ages of 12 and 20 (Kimonis, Frick, Skeem, et al, 2008; see also Fanti, Frick, & Georgiou, 2009). …”
Section: Methodsmentioning
confidence: 90%
“…Items (e.g., "I do not show my emotions to others") are rated on a 4-point Likert scale from 0 (not at all true) to 3 (definitely true). The construct validity of the ICU was supported in a large community sample (n = 1,443) of 13-to 18-year-old nonreferred German adolescents (774 boys and 669 girls; Essau, Sasagawa, & Frick, 2006), as well as an American sample (n = 248) of male and female juvenile offenders (188 boys, 60 girls) between the ages of 12 and 20 (Kimonis, Frick, Skeem, et al, 2008; see also Fanti, Frick, & Georgiou, 2009). …”
Section: Methodsmentioning
confidence: 90%
“…Callous-Unemotional Traits-Youth completed the Inventory of Callous-Unemotional Traits, a measure of hallmark characteristics of juvenile psychopathy linked to delinquency and involvement in violent behavior (Essau et al 2006;Frick 2004;Kimonis et al in press). Youth rated "how well" each of 24 statements described them along a 4-point scale (0 = not at all true… 3 = definitely true).…”
Section: Measures: Common Personal and Social-contextual Risk Factorsmentioning
confidence: 99%
“…As such, the APSD may need to be revised in order to reliably assess individual symptom clusters of psychopathy (e.g., have weak items removed or additional items added). To some extent this has been accomplished for the measurement of CU traits with the self-report Inventory of Callous-Unemotional Traits (ICU; Essau, Sasagawa & Frick, 2006), a measure consisting of 24-items. However, this has not been done for the other dimensions covered by the APSD.…”
Section: Discussionmentioning
confidence: 99%
“…However, this has not been done for the other dimensions covered by the APSD. Problems with the factor structure and internal consistency of some of the ICU subscales have also raised questions about the validity of the ICU (e.g., Essau et al, 2006;Kimonis et al, 2008). Nevertheless, one study conducted by Ansel and colleagues (2014) found that the ICU demonstrated higher internal consistency and stronger correlations with delinquent behavior than the CU subscale of the APSD.…”
Section: Discussionmentioning
confidence: 99%